Partitioning ordinary differential equations using multistep formulas. - Suleiman, Mohamed; Ibrahim, Zarina Bibi; Othman, Khairil Iskandar (World Academy of Science Engineering and Technology, 2008)

(untitled)
This paper focuses on solving Ordinary Differential Equations (ODEs) using partitioning technique known as Intervalwise Partitioning Block (IPB) method which is based on Block Backward Differentiation Formulas (BBDF) and Block Adams Formulas. Method based on BBDF requires Newton-like iteration involving the Jacobian matrix of the ODEs. These matrix operations in the iteration scheme are expensive and require a considerable amount of computational effort. Therefore, IPB technique is developed to reduce the cost of these iterations. Numerical results indicate that the IPB strategy reduce the execution time while accuracy is maintained.